Do marine algal polyphenols have antidiabetic, antihyperlipidemic or anti-inflammatory effects in humans? A systematic review. Issue 12 (13th August 2018) - Murray, Margaret; Dordevic, Aimee L.; Bonham, Maxine P.; Ryan, Lisa
ABSTRACT: Cardiovascular disease and type 2 diabetes are leading causes of morbidity and mortality globally. Marine algal polyphenols have potential to reduce the risk of these conditions, however, little is known about their impact in humans. This systematic review investigates the antidiabetic, antihyperlipidemic and anti-inflammatory effects of marine polyphenols in humans. Scopus, Medline, PsychInfo, Embase and Cochrane Library databases were searched in November 2016. Eligible studies included (1) human adults, (2) marine polyphenol intervention, (3) blood lipid, glucose, insulin or inflammatory marker outcomes, and (4) were a randomized-controlled trial. One postprandial cross-over trial and four parallel design trials were included involving 271 adults. Analysis across studies was performed using Cohen's d effect sizes. Supplementation with polyphenol-rich extracts had small-to-medium positive effects on fasting blood glucose, total cholesterol and LDL-cholesterol; however, there is inadequate evidence as yet to confirm if these are consistent effects. Further randomized-controlled trials should investigate polyphenols from Ecklonia cava and other macroalgal sources, to determine if there is a role for marine polyphenols in reducing the risk factors of chronic disease in humans. (PROSPERO registration number CRD42015016890)